CSR Disclosure: A Temporal Analysis of Italian Listed Companies Websites - Katia Furlotti; Federica Balluchi (European Scientific Journal, ESJ, 2016)
The aims of this paper is to analyze the information in the field of Corporate Social Responsibility (CSR) available by reading the companies’ websites. In this sense, we propose an empirical approach with a temporal analysis of the websites of a group of Italian listed companies and of the information in the field of CSR. Websites are evaluated on the basis of the structure (languages, map site, specific section on the CSR) and the content both for the general aspect and with specific reference to environmental responsibility and relationships with the community This methodology puts in evidence the important use of the Internet as a communication tool, especially in recent years. Many international researches on the topic are a key starting point for this paper. The present research intends to work on in the path outlined by the international studies mentioned in order to develop the analysis with reference to Italian companies, listed on the Italian Stock Exchange, characterized by large size. Specifically, we arise the following research questions: RQ1: Do Italian companies communicate information about their commitment to CSR on their websites, fully exploiting the potential offered by the Internet? RQ2: Do companies that have a specific section devoted to CSR communicate a larger amount of information than companies that offer information in a less structured mode? RQ3: Are there differences in the CSR information provided in the web in different periods of time (2013 and 2016)?